Comparative Study of Crystal Violet Stain and Haematoxylin and Eosin Stain in the Assessment of Mitotic Figures in Dysplastic and Malignant Lesions of Oral Cavity - Nayantrishna Nath (Journal of Krishna Institute of Medical Sciences University, 2021)
Background: Mitotic figures are valuable tool in assessing cellular proliferation and act as a prognostic indicator in dysplastic and malignant lesions of oral cavity. Routinely used Haematoxylin and Eosin (H&E) stain has limitations in clearly distinguishing mitotic figures. Aim and Objectives: To compare the mitotic count in Crystal Violet (CV) stain and H&E stained sections of dysplastic and malignant lesions of oral cavity and to evaluate the efficacy of CV stain in assessing mitotic count in these lesions. Material and Methods: Study sample constituted formalin fixed and paraffin-embedded tissue sections, diagnosed on histopathology as dysplastic and malignant lesions of oral cavity (n = 70). For each case two slides of serial sections were cut, one was stained with H&E and the other with CV stain. The number of mitotic figures under 400X magnification in 10 microscopic fields was recorded and average value was calculated for both stains. Data obtained was statistically analyzed by using unpaired t-test. Results: An average mitotic count in 21 cases of epithelial dysplasia was 0.75 per high power field on H&E stain and 1.07 on CV stain. In 49 cases of Squamous cell carcinoma, it was 2.57 per high power field on H&E stain and 3.35 on CV stain. There was significant increase in mitotic count in CV stained sections when compared with H&E stain with a statistically significant difference showing P<0.001 in both dysplastic and malignant lesions. Conclusion: CV stain can be better alternative in assessing mitotic count, as it is cost-effective and simple procedure.